Interstitial water chemistry at DSDP Leg 79 Holes - Joris M Gieskes; Kirk Johnston; Marcus Boehm (PANGAEA, 1984)
Interstitial water analyses of samples collected at Sites 544-547 of DSDP Leg 79 are presented. In Site 547 chloride concentrations increase to almost 80% of the halite saturation values. Gypsum occurrences in the sediments immediately overlying the halite deposit can be explained in terms of migration of Ca**2+ and SO2**2- from the underlying evaporites. At shallower depths sulfate concentrations decrease rapidly as a result of sulfate reduction processes. The same processes lead to the removal of calcium in the form of calcium carbonate. At Site 547, the chloride concentration depth profile suggests a maximum of dissolved chloride which may be the result of advective flow from nearby (abput 6 km) evaporite salt diapirs.
Supplement to: Gieskes, JM et al. (1984): Interstitial water studies, Leg 79. In: Hinz, K; Winterer, EL; et al. (eds.), Initial Reports of the Deep Sea Drilling Project, Washington (U.S. Govt. Printing Office), 79, 825-834, https://doi.org/10.2973/dsdp.proc.79.134.1984